Studi Kuantitatif tentang Peran Guru dan Budaya Sekolah dalam Pembelajaran Matematika SMP - Herniwati, Nani; Nasuha, Munthoha; Kusrina, Tity (Jurnal Simki Pedagogia, 2026)
This study examines how teacher engagement and school culture contribute to the effectiveness of mathematics learning at the junior high school level. Using a quantitative survey research method, the study involved 260 students proportionally selected from a total population of 797 students at four public junior high schools in Bantarbolang District, Pemalang Regency. Data were collected through a structured questionnaire and analyzed using statistical techniques, including descriptive analysis and linear regression. The results indicate that teacher engagement and the character of the school culture have a rapid impact on student learning achievement in mathematics. Teachers' abilities to manage the classroom, deliver material clearly, and provide emotional support are important factors in improving student learning outcomes. Furthermore, a positive school culture, which emphasizes cooperation, discipline, and academic values, has been shown to foster enthusiasm and faster student learning outcomes in mathematics. These findings emphasize the important role of the educational environment and teacher presence in promoting successful mathematics learning at the junior high school level.